Značilnosti kognitivnih motenj pri Parkinsonovi bolezni - Resnik Robida, Karmen (Rehabilitacija (Ljubljana), 2018)
Parkinson's disease is a neurodegenerative progressive disease which primarily manifests in motor symptoms such as tremor, rigidity, bradykinesia (gradual loss and slowing down of spontaneous movement) and postural instability. Motor symptoms manifestation is the key in clinical diagnosis, however in the last decade the research increasingly focuses on the non-motor symptoms of the disease. The cognitive changes in Parkinson's disease are linked to functional and structural changes in the brain and are not similar to other neurodegenerative diseases. Mild cognitive impairment may have a predictive value for dementia. Research shows that early deficits in the visual-spatial and memory domains are a better predictor of the progression to dementia compared to deficits in executive functions, which are mainly a result of fronto-striatal pathway changes modified by dopaminergic system. It is important to detect early cognitive changes in PD in order to offer an individualised therapeutic support.
Keywords: blaga kognitivna motnja; cognition; demenca; dementia; kognicija; mild cognitive impairmen; Parkinson Disease; Parkinsonova bolezen; Parkinson's disease; psychology